2022
DOI: 10.1093/ecco-jcc/jjab232.650
|View full text |Cite
|
Sign up to set email alerts
|

P523 Effectiveness of biological treatments for inflammatory bowel disease in the elderly patients

Abstract: Background Biological treatments used for the treatment of inflammatory bowel disease (IBD) have demonstrated their efficacy and safety, although these results were obtained from studies that mostly include young people generally included in clinical trials. The objective of our study is to assess the efficacy of these treatments in the elderly population in real life Methods Patients have been retrospectively included with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A retrospective study done on 1090 elderly patients with IBD indicated that biological drugs have response rates like those of young and adult population, golimumab being the drug that had to be discontinued most frequently due to ineffectiveness in the older adult population [15].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…A retrospective study done on 1090 elderly patients with IBD indicated that biological drugs have response rates like those of young and adult population, golimumab being the drug that had to be discontinued most frequently due to ineffectiveness in the older adult population [15].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%